Research, Writing, and Creative Process in Open and Distance Education Tales from the Field - Conrad, Dianne (Open Book Publishers, 2023)
This collection of reflective essays is a treasure trove of advice, reflection and hard-won experience from experts in the field of open and distance education. Each chapter offers tried-and-tested advice for nascent academic writers, delivered with personal, rich, and wonderful stories of the authors' careers, their process, their research and their writing, and the struggles and triumphs they have encountered in the course of their careers. The contributors explore the philosophies that guide their work, the conflicts and barriers they have overcome and the mentors and opportunities that sustain and stimulate them, always focused on making their experiences relevant and useful for scholars who are in the early stages of their writing lives. These rich and informative essays will appeal to anyone who wants to learn more about the crafts of research and writing, and the unseen struggles involved in publishing and "being heard."